Analysis of The Science Experiment of Colour Mixing from Natural Materials in Group A Children at Aisyiyah 1 Cakra Kindergarten - Zalza Aprilian Syahbi; Najwa Tussholihah; Lale Dewi Nurlita Safitri; Aa Sukarso (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Science learning in early childhood can be enhanced through meaningful, hands-on activities. This study aims to analyze the implementation of a science experiment involving colour mixing using natural materials with children in Group A at Aisyiyah 1 Cakra Kindergarten. The research employed a descriptive qualitative method with simple activity-based science experiments. The subjects consisted of 15 children aged 4 to 5 years. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results showed that science experiments using natural materials encouraged children to verbally express their observations and recognize various colours and ingredients such as purple, red, turmeric, and pandanus leaves. These activities stimulated children's creativity and supported their social-emotional development through imagination, task-sharing, discussions, and collaboration in small groups. The study concludes that science experiments based on natural materials are practical in enriching early childhood learning. It is recommended that educators implement similar activities to improve children's cognitive, language, and social skills through active and collaborative learning experiences.